Impact analysis of inbuilt rehabilitation material on the recultivation of abandoned sandpit - Sonja CERAR; Špela BAVEC (Acta Agriculturae Slovenica, 2019)
For the rehabilitation and reclamation of abandoned sandpit in Drtija (Moravče), construction composites are used as rehabilitation materials. Construction composites are produced by mixing of recycled non-hazardous waste and natural materials. In the presented study, the chemical composition of the rehabilitation materials, which are already built-in on abandoned surfaces and impact analysis on recultivation of the upper layer, was evaluated. For this purpose, the rehabilitation materials were sampled at 3 locations with test pit excavations up to a depth of 3 m, surrounding topsoils (0-10 cm) at 2 locations and leachate at 1 location. The results show that the in-built rehabilitation materials are burdened with metals (Cd, Cr, Cu, Ni, Pb, Zn), which are, however, poorly soluble under the given conditions. The latter is also indicated by the concentrations of metals in the leachate, which are within the lower limit of quantification (LOQ) area. Regarding organic substances, the presence of phenol and formaldehyde was found in the leachate. In rehabilitation materials only phenol was found in two samples. Considering that the rehabilitation materials will be covered with a layer of clay and humus and will be tilled or afforested as part of the final rehabilitation step, the impact of rehabilitation materials on the reclaimed soil is not expected. According to results of this study recultivaton of the upper layer with planting of woods is recommended.